Value Added Analysis of Strawberries at Each Supply Chain Actor in Nagari Balingka, Agam Regency - Siska Kostantia; Santosa Santosa; D.A. Permata (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Strawberries are a high-value horticultural commodity with a short shelf life, which results in involvement of multiple actors along their supply chain and differences in value creation. This study aims to analyze the value added of strawberries at each main supply chain actor in Nagari Balingka, Agam Regency. The research was conducted from January to August 2025 using a survey method involving strawberry farmers, collectors, wholesalers, and retailers. Value-added analysis was carried out using the Hayami method to calculate value added, value-added ratio, profit, and profit rate for each actor. The results show that farmers generate the highest value added, ranging from Rp 22,852 to Rp 57,140 per kg with a value-added ratio of 46-88%, which is classified as high. In contrast, collectors, wholesalers, and retailers produce lower value-added, with value-added ratios ranging from 7% to 26%, classified as low to moderate. Differences in value added and profits among actors are influenced by raw material prices, selling prices, and other input costs. Overall, the largest value creation in the strawberry supply chain occurs at the farmer level, while downstream actors mainly function as intermediaries with relatively limited margins. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 8: Decent Work and Economic Growth